2013
DOI: 10.3917/adh.124.0065
|View full text |Cite
|
Sign up to set email alerts
|

Rester ou repartir ? Une analyse des usages de la ville par les migrants dans la Genève des années 1837-1843

Abstract: Si les études historiques récentes mettent en évidence d’importants mouvements migratoires avant la révolution industrielle, elles soulignent également leur nature majoritairement temporaire. Pour l’essentiel des immigrants, l’arrivée dans une ville n’est qu’une étape dans un parcours parfois sinueux qui est déterminé à la fois par leurs attentes et les conditions d’accueil qu’ils rencontrent sur leur chemin. Cette étude, qui s’appuie sur les permis de séjour de la ville de Genève entre 1837 et 1843, vise à re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Em que diz respeito ao habitus migratório, Remund (2009) explica que a noção corresponde à "parte do projeto migratório que independe das características pessoais do migrante"as atitudes e comportamentos herdados de sua comunidade de origem por meio dos mecanismos de socialização, e que são, por sua vez, decorrentes das práticas migratórias das gerações anteriores. O que explica, segundo o mesmo autor, a "articulação direta entre a dimensão pessoal de maturação dos projetos migratórios e a criação de fluxos massivos de mobilidade", constituindo verdadeiros sistemas migratórios dotados de "estruturas estáveis e duradouras, com tradições migratórias profundamente enraizadas, e que muitas vezes se estendem de uma geração a outra" (Remund, 2009, p. 125, tradução nossa).…”
Section: Espaço Social E Habitus Migratóriounclassified
“…Em que diz respeito ao habitus migratório, Remund (2009) explica que a noção corresponde à "parte do projeto migratório que independe das características pessoais do migrante"as atitudes e comportamentos herdados de sua comunidade de origem por meio dos mecanismos de socialização, e que são, por sua vez, decorrentes das práticas migratórias das gerações anteriores. O que explica, segundo o mesmo autor, a "articulação direta entre a dimensão pessoal de maturação dos projetos migratórios e a criação de fluxos massivos de mobilidade", constituindo verdadeiros sistemas migratórios dotados de "estruturas estáveis e duradouras, com tradições migratórias profundamente enraizadas, e que muitas vezes se estendem de uma geração a outra" (Remund, 2009, p. 125, tradução nossa).…”
Section: Espaço Social E Habitus Migratóriounclassified
“…Staying and settling durably was a very selective process. Most of the immigrants came from neighboring France and French-speaking Switzerland, but also from German-speaking Switzerland and Germany, and from northern Italy (Remund, 2009;Ryczkowska, 2013;Schumacher, 2010). Adrien Remund (2010;2012) has shown that a third of the migrants left after three months, half of them after one year.…”
Section: Vulnerable Populations Vulnerable Womenmentioning
confidence: 99%
“…Most of the immigrants came from neighboring France and French-speaking Switzerland, but also from German-speaking Switzerland and Germany, and from northern Italy (Remund, 2009;Ryczkowska, 2013;Schumacher, 2010). Adrien Remund (2010;2012) has shown that a third of the migrants left after three months, half of them after one year. Later on, departures remained high until reaching approximately 10% of the initial cohort of immigrants.…”
Section: Vulnerable Populations Vulnerable Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe it is elucidating to compare such different cases in order to develop a transversal approach to cities' hospitality towards newcomers. Both urban areas have a long history of migration and a large population of foreign origin, and both continue to receive newcomers who challenge their (in)hospitality (Necker, 1995;Rea, 2013;Remund, 2012;Wauters, 2017).…”
Section: Investigating Newcomers In Brussels and Genevamentioning
confidence: 99%